Salivary Alpha-Amylase Enzyme, Psychological Disorders, and Life Quality in Patients with Recurrent Aphthous Stomatitis - Juliana Andrade Cardoso; André Avelino dos Santos Junior; Maria Lucia Tiellet Nunes; Maria Antonia Zancanaro de Figueiredo; Karen Cherubini; Fernanda Gonçalves Salum (Hindawi Limited, 2017)
Objective. The aim of this study was to evaluate stress, anxiety, and salivary alpha-amylase (SAA) activity in patients with recurrent aphthous stomatitis (RAS). The impact of this disease on the life quality was also evaluated. Design. Twenty-two patients with RAS and controls, matched by sex and age, were selected. Stress and anxiety were assessed using Lipp's Inventory of Stress Symptoms and Beck Anxiety Inventory. Life quality was assessed through the World Health Organization Quality of Life-bref (WHOQOL-BREF) and the Oral Health Impact Profile-14 (OHIP-14). Saliva samples were collected in the morning and afternoon and the SAA activity was analyzed by enzymatic kinetic method. Results. No significant difference was observed between the groups regarding the SAA activity (p=0.306). Patients with RAS had higher scores of anxiety (p=0.016). The scores of WHOQOL-BREF were significantly lower in patients with RAS. The values obtained through OHIP-14 were significantly higher in these patients (p=0.002). Conclusion. RAS negatively affects the life quality. Patients with the disease have higher levels of anxiety, suggesting its association with the etiopathogenesis of RAS.